2015
DOI: 10.1002/biot.201400705
|View full text |Cite
|
Sign up to set email alerts
|

Steam explosion and its combinatorial pretreatment refining technology of plant biomass to bio‐based products

Abstract: Pretreatment is a key unit operation affecting the refinery efficiency of plant biomass. However, the poor efficiency of pretreatment and the lack of basic theory are the main challenges to the industrial implementation of the plant biomass refinery. The purpose of this work is to review steam explosion and its combinatorial pretreatment as a means of overcoming the intrinsic characteristics of plant biomass, including recalcitrance, heterogeneity, multi-composition, and diversity. The main advantages of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 110 publications
(18 reference statements)
0
60
0
Order By: Relevance
“…various degradation products (Sharma et al, 2015;Mood et al, 2013;Agbor et al, 2011). Corn stover, corncob, and other agricultural stalks are rich in hemicellulose, which is the second most abundant polysaccharide in nature (Mood et al, 2013;Chen and Liu, 2015). The ultimate goal of biomass refinery is 'zero waste', meaning that all sugars or carbons fixed in lignocellulosic biomass must be utilized efficiently (Zeng et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…various degradation products (Sharma et al, 2015;Mood et al, 2013;Agbor et al, 2011). Corn stover, corncob, and other agricultural stalks are rich in hemicellulose, which is the second most abundant polysaccharide in nature (Mood et al, 2013;Chen and Liu, 2015). The ultimate goal of biomass refinery is 'zero waste', meaning that all sugars or carbons fixed in lignocellulosic biomass must be utilized efficiently (Zeng et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Lignocellulosic biomass, which can be converted into alternative fuels such as ethanol, should be the primary energy resource due to its high annual production worldwide (1 Â 10 10 MT/year) (Alvira et al, 2010;Chen and Qiu, 2010). It can be obtained as the wastes of the agriculture and forestry industries, or from energy crops especially cultivated for the purpose (Chen and Liu, 2015;Ko et al, 2015). Corn stover is a potential feedstock for ethanol production due to high sugar content and low price of preparation (Ou et al, 2014;Luo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the isolated 5-HMF wasc onfirmed by 1 Ha nd 13 CNMR spectroscopy ( Figures S2-S4). The purity of the isolated 5-HMF was confirmedb yq uantitative 13 CNMR spectroscopy ( Figure S2) and revealed that isobutanol is an admixture.…”
Section: Extraction Of 5-hmf With Organic Solventsmentioning
confidence: 90%
“…[8] The main products of its processing are holocellulose and cellulose. They can be separated from lignin by various pretreatment methods, [9] including hydrolysis with dilute and concentrated sulfuric acid, [10] alkaline hydrolysis, [11] the organosolv process, [12] steam explosion, [13] ammonia fiber explosion (AFEX), [14] etc. The relative simplicity of cellulose processing allows aw ide variety of products that are so-called "platform molecules" for industrial applicationst ob eo btained.…”
Section: Introductionmentioning
confidence: 99%
“…A number of alternative pre-treatment technologies are currently being applied for the intensification of biomass and waste, which include ultrasound assisted processing [34][35][36][37], steam explosion [38][39][40], ammonia fiber explosion (AFEX) [41][42][43], and extrusion [44][45][46].…”
Section: Applications Of Microwave Heating To Pre-treat Biomassmentioning
confidence: 99%